FURUNCULOSIS IN SNOW TROUT (SCHIZOTHORACINAE) IN KASHMIR: FIRST REPORT - Chalkoo, Salman Rauoof; Najar, A. M.; Qureshi, T. A.; Shafi, Aamira (Journal of Indian Fisheries Association, 2007)
Incidences of furunculosis were reported in Schizothorax spp.(Schizothorax niger, S. esocinus, S. curvifrons and S. labiatus) in Wular Lake,Kashmir, from 2003 to 2005. The disease was reported during summer and winter months, but the percentage of infection was maximum during winter.Mortality rate ranged from 8 to 15%. Artificial challenge of Schizothorax spp. with Aeromonas salmonicida produced symptoms pertinent to furunculosis. The incidence of disease was the highest (13.87 %) in December, and lowest (0.40%) in May and October. S. esocinus exhibited the maximum ( 44.48%) percentage of infection, while asS. labiatus exhibited the minimum (14.28%) throughout the study period. Haematological investigations revealed devastating changes in various blood parameters. Chemotherapeutic tests revealed complete recovery of the disease using 20 ppm oxytetracycline and 30 ppm streptomycin.Keywords: Furunculosis, Aero monas salmonicida,Schizothoracinae, treatment